Effect of Certain Hospital-related Factors on the Implementation of the Nursing Process: Nurses' Perspective at Chuka Level 5 Hospital, Kenya - Beth Gichobi; Lucy Gitonga; Immaculate Marwa (KHD-Production, 2024)
Nursing Process is a proven means of standardizing patients` care and maintaining the autonomy of the nursing profession. It is considered globally as a standard tool which gives nurses opportunity of caring for patients in a scientific, holistic, and flexible way (1, 2). If nursing process is utilized properly, it enables nurses to offer independent care to patient (2), However, certain hospital-related factors are thought to influence nurses` implementation of the nursing process (3). To assess Nurses` perspective on the effect of certain Hospital-related factors on implementation of the Nursing Process in Chuka level 5 Hospital in Kenya. A cross-sectional survey done at Chuka level 5 hospital in Kenya. Study population were nurses working in Chuka hospital. Simple random sampling was used to get 30 nurses to make the study sample. Questionnaires were employed for data collection. Data summary was done using descriptive statistics and presented in tables. Study participants` mean age was 37.2 (±9.3) with majority being females (46.7% (n=14)), married (76.7% (n=23)), and with diploma qualification (56.7 % (n=17)). The majority of the study participants felt that status of a number of hospital related factors that play critical part in implementation of the nursing process were inadequate with staffing, resources availability leading in the inadequate verdict by over 70% of the study participants. Majority (80%) of the participants felt that the nurse-patient ratio was negatively influencing their ability to implement the nursing process. However, they were more or less equally divided on their perception as to whether each of the remaining factors were influencing their utilization of the nursing process either positively or negatively. The study participants reported the presence of inadequacy of hospital-related factors which negatively impacted on their implementation of the nursing process. Hospital management should prioritize the implementation of the nursing process by allocating adequate resources and proving active leadership on the same, as it is key in the delivery of quality nursing care.